2022
DOI: 10.3389/fimmu.2022.859954
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cell Therapy Is More Cost-Effective Than Fecal Diversion for Treatment of Perianal Crohn’s Disease Fistulas

Abstract: Crohn’s disease (CD) is an inflammatory bowel disease with increasing incidence and prevalence worldwide. Perianal fistulas are seen in up to 26% of CD patients and are often refractory to medical therapy. Current treatments for CD perianal fistulas (pCD) include antibiotics, biologics, and for refractory cases, fecal diversion (FD) with ileostomy or colostomy. Mesenchymal stem/stromal cell therapy (MSCs) is a new modality that have shown efficacy in treating pCD. MSCs locally injected into pCD can lead to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The self-renewal, in vitro expandability, multipotent differentiation capacity, being less prone to senescence, and non-immunogenic but still immunomodulatory properties of MSCs from various tissue sources have attracted researchers for their clinical applications in the field of regenerative diseases ( Zhang et al, 2015 ; Alessio et al, 2018 ; Alessio et al, 2019b ). MSCs are candidates for cell-based therapeutic strategies for various disease conditions including neurodegenerative disorders, where clinical stabilization of non-option Parkinsonism was observed for at least 6 months, improvements observed in cardiovascular diseases, perianal fistulas associated with Crohn’s disease, COVID-19, bone disorders, and cancers ( Giordano et al, 2014 ; Canesi et al, 2016 ; Kastrup et al, 2017 ; Liu S. et al, 2020 ; Cheng et al, 2020 ; Hmadcha et al, 2020 ; Wang et al, 2021 ; Johnson et al, 2022 ; Shi et al, 2022 ; Sohrabi et al, 2022 ). A clinical trial on the safety and feasibility of adipose-derived stromal cells also demonstrated a safe and feasible treatment of ischemic heart diseases and heart failure ( Kastrup et al, 2017 ).…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%
“…The self-renewal, in vitro expandability, multipotent differentiation capacity, being less prone to senescence, and non-immunogenic but still immunomodulatory properties of MSCs from various tissue sources have attracted researchers for their clinical applications in the field of regenerative diseases ( Zhang et al, 2015 ; Alessio et al, 2018 ; Alessio et al, 2019b ). MSCs are candidates for cell-based therapeutic strategies for various disease conditions including neurodegenerative disorders, where clinical stabilization of non-option Parkinsonism was observed for at least 6 months, improvements observed in cardiovascular diseases, perianal fistulas associated with Crohn’s disease, COVID-19, bone disorders, and cancers ( Giordano et al, 2014 ; Canesi et al, 2016 ; Kastrup et al, 2017 ; Liu S. et al, 2020 ; Cheng et al, 2020 ; Hmadcha et al, 2020 ; Wang et al, 2021 ; Johnson et al, 2022 ; Shi et al, 2022 ; Sohrabi et al, 2022 ). A clinical trial on the safety and feasibility of adipose-derived stromal cells also demonstrated a safe and feasible treatment of ischemic heart diseases and heart failure ( Kastrup et al, 2017 ).…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%